Can integrative biomarker approaches improve prediction of platinum and PARP inhibitor response in ovarian cancer?. (December 2021) - Funingana, Ionut-Gabriel; Reinius, Marika A.V.; Petrillo, Angelica; Ang, Joo Ern; Brenton, James D.
Abstract: Epithelial ovarian carcinoma (EOC) encompasses distinct histological, molecular and genomic entities that determine intrinsic sensitivity to platinum-based chemotherapy. Current management of each subtype is determined by factors including tumour grade and stage, but only a small number of biomarkers can predict treatment response. The recent incorporation of PARP inhibitors into routine clinical practice has underscored the need to personalise ovarian cancer treatment based on tumour biology. In this article, we review the strengths and limitations of predictive biomarkers in current clinical practice and highlight integrative strategies that may inform the development of future personalised medicine programs and composite biomarkers.